The effect of high intensity functional training on the oxidative status, muscle damage and performance of basketball players - Hovsepian, A.; Esfarjani, F.; Bambaeichi, E.; Zolaktaf, V. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: The purpose of this study was to evaluate the effect of 10 weeks of two different in-season training programs on the oxidative status and muscle damage and performance of professional basketball players. We hypothesized that high intensity functional training (HIFT) induces more redox sensitive adaptations than common strength and conditioning training (CSCT). METHODS: Twenty professional basketball players of Iran national women`s basketball league (age 21.95±2.45, years of experience 7.15±1.7), were divided into two equal training groups; HIFT and CSCT (in average of 80-150 and 180-240 minutes per week respectively). Blood samples and performance tests including VO2max, basketball simulated performance (BEST), anaerobic power, agility and vertical jump were taken before and after training. Oxidative status and tissue damage were assessed through xanthine oxidase, total antioxidant capacity, pro-oxidant/antioxidant balance and creatine kinase. Data were analyzed through repeated measure mixed ANOVA. RESULTS: BEST, average power and Fatigue Index significantly improved in HIFT group (a<0.05). VO2max and agility t-test improved significantly in both groups (a<0.05), with no significant difference between the two groups. Lateral agility and vertical jump did not change significantly in neither of the groups. No significant group × time interaction was observed in the biochemical factors. XO increased, TAC and CK decreased significantly in both groups (a<0.05), with no significant change in PAB in neither of the groups after training. CONCLUSIONS: The findings of the present study showed no oxidative stress and tissue damage in none of the training groups, recommending the implication of more time-efficient HIFT method into the in-season training of team sports.